Production Cost Accounting - Zinkevičienė, Danutė (Ekonomika, 1997)
The solution to management problems requires reliable cost accounting information. At present, the creation of this kind of information is conditioned by the requirements of the financial account and the financial account statement plan. Nevertheless, the model statement plan does not provide a successfully reorganized account of production cost and manufactured products. It is suggested that the sixth class of the statement plan be named “Cost.” Production costs and manufactured products can be included in 61 accounts of direct production costs and 62 indirect production costs of this class. Cost accounting detailization of special features should be presented in the registers of analytical accounting.